Assimilation of radar quantitative precipitation estimations in the Canadian Precipitation Analysis (CaPA) - Fortin, Vincent; Roy, Guy; Donaldson, Norman; Mahidjiba, Ahmed (Journal of hydrology (Amsterdam), 2015)
•The configuration of the Canadian Precipitation Analysis (CaPA) system is presented.•It provides gridded precipitation estimates on a 10-km grid for North America.•We examine the added value of weather radar data for CaPA.•The skill of the gridded precipitation product is significantly improved in summer.•The gridded precipitation product is available online in near real-time. The Canadian Precipitation Analysis (CaPA) is a data analysis system used operationally at the Canadian Meteorological Center (CMC) since April 2011 to produce gridded 6-h and 24-h precipitation accumulations in near real-time on a regular grid covering all of North America. The current resolution of the product is 10-km. Due to the low density of the observational network in most of Canada, the system relies on a background field provided by the Regional Deterministic Prediction System (RDPS) of Environment Canada, which is a short-term weather forecasting system for North America. For this reason, the North American configuration of CaPA is known as the Regional Deterministic Precipitation Analysis (RDPA). Early in the development of the CaPA system, weather radar reflectivity was identified as a very promising additional data source for the precipitation analysis, but necessary quality control procedures and bias-correction algorithms were lacking for the radar data. After three years of development and testing, a new version of CaPA–RDPA system was implemented in November 2014 at CMC. This version is able to assimilate radar quantitative precipitation estimates (QPEs) from all 31 operational Canadian weather radars. The radar QPE is used as an observation source and not as a background field, and is subject to a strict quality control procedure, like any other observation source. The November 2014 upgrade to CaPA–RDPA was implemented at the same time as an upgrade to the RDPS system, which brought minor changes to the skill and bias of CaPA–RDPA. This paper uses the frequency bias indicator (FBI), the equitable threat score (ETS) and the departure from the partial mean (DPM) in order to assess the improvements to CaPA–RDPA brought by the assimilation of radar QPE. Verification focuses on the 6-h accumulations, and is done against a network of 65 synoptic stations (approximately two stations per radar) that were withheld from the station data assimilated by CaPA–RDPA. It is shown that the ETS and the DPM scores are both improved for precipitation events between 0.2mm and 25mm per 6-h, and that the FBI is unchanged.